ANALYSIS AND PROBLEMS OF ONLINE MEDIA USE TOWARDS STUDENT LEARNING IN CLASS VIII SMP NEGERI 1 SITINJO DISTRICT DAIRI ACADEMIC YEAR 2020/2021 - Winarto Silaban (Jurnal Scientia, 2022)
The learning conditions of students while studying at home have been 10 months, so that they are bored and finally lazy. Teachers find it difficult to provide motivation in the learning process because students also feel that they are not supervised, moreover both of their parents are working, so there is no one to guide them to study, while the learning process takes place in the morning until noon. To measure student learning outcomes, this is a problem experienced by teachers because of the difficulty of students in capturing or understanding every indicator conveyed during online learning, even though learning indicators have been repeatedly conveyed by teachers through learning media such as google classroom, zoom, WhatsUp, and others. other. Students sometimes even don't open Google Classroom at all, even though all the material and explanations have been delivered. This makes it difficult for the teacher to find out whether the student has understood what is being conveyed to achieve the predetermined Minimum Completeness Criteria (KKM). and those who stated that they were not at all interested were in the percentage of 65%, and additional problems in learning accompanied by the carrying capacity of purchasing a low internet quota were in the range of 62% below Rp. 50,000, - and those who did not have an internet quota in the range of 3%.